EVALUASI PROGRAM PELAKSANAAN PRAKTEK KERJA LAPANGAN (PKL) PROGRAM KEAHLIAN TEKNIK FURNITUR PADA SMK NEGERI DI DKI JAKARTA - Asmarayani, Erni; Rusmono; Rahmayanti, Henita (Jurnal Pendidikan Teknik dan Vokasional, 2020)
This study aims to obtain information on how far the policy of Field Work Practice program (PKL) on the Department of Furniture Engineering at SMK Negeri in DKI Jakarta, which has been held several years with several industries. Furthermore, this study also aims to see what components that can affect the impact of Field Work Practice (PKL). The evaluation research is oriented to record how far the implementation of PKL Program of Engineering Furnitur at SMK Negeri in DKI Jakarta. By looking at the contex components, inputs, processes, products that have been implemented using the CIPP model approach. Data collection techniques can be done by observation (observation), interview (interview), questionnaire (questionnaire), and documentation (data storage). The result of descriptive analysis shows that at the context stage is Program Planning aspect, Government Policy and Legality (MoU) with Industrial World in Good category. Similarly for the stage of Input on the aspect of Academic, Curriculum, Facilities and Infrastructure as well as Financing included in the category of Good, the process stage includes aspects of curriculum and teaching materials, teaching and learning activities as well as cost in the category of Good, for the product stage that includes students' in the category of Good, to be made in the improvement of the implementation of the PKL convey some suggestions: for the context of planning, objectives, policies of street vendors must be made more clear and directed and Cooperation (MoU) expanded by involving the Ministry of Education and Ministry of Manpower. For Input, readiness of students, teachers, facilities and infrastructure and tools and materials are often updated in order to keep up with the development of the furniture industry. For the process of organizational activities, teachers and students in learning activities are improved continuously with appropriate methods of development of the furniture industry. For the product in achieving the target pass 100% competence exam and 100% get value ≥ 7.00 can be achieved continue to practice and enhanced student competence. Keywords: CIPP model, context, innput, process, product.